Quantitative assessment of ground deformation risks, controlling factors and movement trends for onshore petroleum and gas industry using satellite Radar remote sensing and spatial statistics. Issue 2 (3rd April 2022) - Bayramov, Emil; Buchroithner, Manfred; Kada, Martin; Bayramov, Rafael
ABSTRACT: A number of productive oil and gas fields are located in the Absheron Peninsula of Azerbaijan. The primary goal of the presented study was to quantitatively assess the ground deformation (subsidence and uplift) rates of oil and gas fields, determine natural and man-made influencing factors and predict deformation trends. Persistent Scatterer Interferometric Synthetic Aperture Radar technique was used for the present studies to detect ground deformation rates and velocities in the Absheron oil and gas fields. The existence of ground deformation processes was observed for the period of 2015–2017 with three hotspots of highest subsidence rates and three hotspots of highest uplift rates in oil and gas fields. The determined maximum displacement rates of subsidence and uplift processes were −26 mm/y and +23 mm/y, respectively. However spatial density analysis of deformation velocity presented the natural patterns of uplift and subsidence tectonic processes. This allowed to determine that two oil and gas fields hold a higher probability of being affected by man-made oil and gas exploration activities, whereas the one oil field is affected by both natural and man-made processes. Geographically Weighted Regression analysis revealed that well concentration and elevation factors provided 32% of explanation to subsidence processes.